A Possible Reason to Induce Acute Graft-vs.-Host Disease After Hematopoietic Stem Cell Transplantation: Lack of Sirtuin-1 in CD4+ T Cells - Xu, Ya-jing; Chen, Fang-ping; Chen, Yan; Fu, Bin; Liu, En-yi; Zou, Lang; Liu, Lin-xin (Frontiers in Immunology, 2018)
Sirtuin 1 (SIRT1) is a critical suppressor of T cell immunity. However, whether SIRT1 is involved in the progression of acute graft-versus-host disease (aGVHD) has still remained unclear. PI3K/Akt/mTOR pathway is a crucial element involved in the activation and functions of T cells. Over-activation of PI3K/Akt/mTOR signaling may be related to the occurrence of aGVHD. STAT3 activation requires phosphorylation and acetylation. A recent study showed that STAT3 hyperphosphorylation in CD4+ T cells may be a trigger of aGVHD. The role of the STAT3 acetylation in aGVHD pathogenesis is still unclear. The present study revealed that SIRT1 deficiency as a critical factor is involved in the excessive activation of mTOR pathway and upregulation of STAT3 acetylation and phosphorylation in CD4+ T cells from patients with aGVHD. Exorbitant activation of IL-1β signaling is the main reason for TAK1-dependent SIRT1 insufficiency. The findings of the present study might provide a new therapeutic target for treating aGVHD.